A comparative analysis on harmony and arrangement of David Foster's "through the fire" case study: Through the Fire by Chaka Khan & through the fire by Renee Olstead / Mohd Firdaus Abd Wahab - Abd Wahab, Mohd Firdaus (2007)
Generally, this study has been conducted to make a comparative on harmony and music arrangement of David Foster's "Through The Fire". Therefore, this study looks forward to a sympathetic of tips and secret that makes David Foster become successful in his career life of music with an unique idea in his composition and arrangement. This research also has been analyzed on the harmonic structure, and the music arrangement between two different versions of "Through the Fire". In conclusion, the study has revealed that David Foster clearly like to uses diatonic harmony with some usage of secondary and subdominant in his composition. He also knows to uses the inversion of the chords to create a smooth and linear bass motion with structured and well-organized chords.